Export Restrictions and Price Insulation during Commodity Price Booms - Martin, Will (2012)
For individual countries, variable trade barriers can be used to reduce the volatility of domestic relative to world prices. If this is done by countries accounting for a large share of the market, its effect is offset by increases in world price volatility. This study shows the nature of the resulting collective action problem, with the policy being ineffective on average in stabilizing domestic prices while increasing the volatility of the income transfers from terms-of-trade changes. A simple approach to assessing the contribution of insulation to the price increases is developed and used with new estimates of agricultural distortions to assess its contribution to the price spikes in 1972-74 and 2006-08 for rice and wheat. The analysis suggests that 45 percent of the increase in rice prices in 2006-08, and 30 percent of the increase in wheat prices, was due to insulating behavior. One sign of progress since 1972-74 was a substantial reduction in the extent of price-insulating behavior by the industrial countries. This provides little stabilizing benefit in the rice market because countries not classifying themselves at the World Trade Organization as developing account for only 3 percent of world rice consumption. But it does offer some benefit for the wheat market where non-developing countries account for 27 percent of consumption.